Caracterização do Perfil Sócio-Demográfico de Gestantes Adolescentes: Revisão da Literatura Brasileira - Levandowski, Daniela Centenaro (2009)
This study aims a bibliographic research of Brazilian studies published from 1987 to 2007, which scrutinizes the socio-demographic profile of pregnant teenagers attended in public health institutions. From a research done in search sites (Scielo, BVS-Psi, Google Schoolar), it was found 23 papers about this subject that were analyzed in relation to informed features of pregnant teenagers. In general the age average considered was from 10 to 19 years, and the numbers of pregnant girls was higher in low socioeconomic level in teenagers with 17 years old. It also became evident the lack of information about relational and familiar aspects, that can difficult the planning of interventions with this population. Furthermore, it is suggested that future studies could add other relevant information for the characterization of a broad socio-demographic profile, including information about adolescent’s partner and parents.